Medicinal Plants in the Treatment of Depression. II: Evidence from Clinical Trials - Moragrega, Inés; Ríos, José Luis (Planta Medica, 2021)
Depression is a syndrome characterized by deep sadness and the inhibition of psychic functions, sometimes accompanied by neurovegetative disorders, with symptoms of anxiety almost always present. The disease produces alterations in a variety of neural networks and neurotransmission systems, along with a dysfunction of the hypothalamic-pituitary-adrenal axis, which leads to concomitant alterations in the immunological response. Generally, there is a parallel increase in proinflammatory mediators as well as oxidative and nitrosative damage caused by a reduction of antioxidant defenses. In a previous review, we compiled and examined studies of medicinal plants that had been evaluated in preclinical assays, including existing data on 155 species studied and reported as antidepressants or as sources of active principles for treating this condition. This review will thus limit its focus to the 95 clinical trials found in PubMed among the 670 articles on antidepressant-like medicinal plants. To this end, we have reviewed the publications cited in the Cochrane Database of Systematic Reviews, PubMed, and the Science Citation Index from 2000 to 2020. Our review emphasizes those species that have demonstrated the greatest pharmacological potential when studied for their antidepressant properties in humans through clinical trials. Saffron, turmeric, St. Johnʼs wort, ginkgo, kava, and golden root are the most relevant plants that have provided important evidence for the treatment of depression in clinical trials.
Keywords: antidepressant; medicinal plants; clinical trials; natural products; curcumin; saffron